Central precocious puberty in Prader-Willi syndrome: a narrative review - Nicoară, Delia-Maria; Scutca, Alexandra-Cristina; Mang, Niculina; Juganaru, Iulius; Munteanu, Andrei-Ioan; Vitan, Luiza; Mărginean, Otilia (Frontiers in Endocrinology, 2023)
Prader Willi syndrome (PWS, OMIM176270) is a rare genetic disorder with recognizable dysmorphic features and multisystemic consequences such as endocrine, neurocognitive and metabolic ones. Although most patients with Prader-Willi syndrome exhibit hypogonadotropic hypogonadism, there is variability regarding sexual maturation, with precocious puberty occurring in rare cases. Our aim is to elaborate a thorough review of Prader-Willi patients with central precocious puberty, in order to raise awareness of such cases and to enhance our knowledge regarding the diagnosis and prompt treatment of this particular PWS patients.